ChemInform Abstract: Microwave Synthesis of Chiral N‐Benzyl‐2‐methyl‐2H‐benzo[b][1, 4]oxazin/thiazin‐3(4H)‐ones via Smiles Rearrangement and Their Biological Evaluation. Issue 40 (12th September 2013) - Meng, Li‐juan; Zuo, Hua; Vijaykumar, B. V. D.; Dupati, Gautam; Choi, Kyung‐Min; Jang, Kiwan; Yoon, Yon‐Jin; Shin, Dong‐Soo
Abstract Most of the synthesized compounds (V) show good inhibition against Gram positive bacteria and fungi.